Humanizing Digital Reality Design Modelling Symposium Paris 2017 - De Rycke, Klaas; Gengnagel, Christoph; Baverel, Olivier; Burry, Jane.; Mueller, Caitlin; Nguyen, Minh Man.; Rahm, Philippe; Thomsen, Mette Ramsgaard; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book aims at finding some answers to the questions: What is the influence of humans in controlling CAD and how much is human in control of its surroundings? How far does our reach as humans really go? Do the complex algorithms that we use for city planning nowadays live up to their expectations and do they offer enough quality? How much data do we have and can we control? Are today's inventions reversing the humanly controlled algorithms into a space where humans are controlled by the algorithms? Are processing power, robots for the digital environment and construction in particular not only there to rediscover what we already knew and know or do they really bring us further into the fields of constructing and architecture? The chapter authors were invited speakers at the 6th Symposium "Design Modelling Symposium: Humanizing Digital Reality", which took place in  Ensa-Versailles, France from 16 - 20 September 2017.   .
Data and Design: Using Knowledge Generation/Visual Analytic Paradigms to Understand Mobile Social Media in Urban Design -- This room is too dark and the shape is too long: quantifying architectural design to predict successful spaces -- The design implications of form-finding with dynamic topologies -- A Multi-Scalar Approach for the Modelling and Fabrication of Free-form Glue-laminated Timber Structures -- Stone Morphologies: Erosion-Based Digital Fabrication through Event-Driven Control -- Simulating pedestrian movement -- Automated Generation of Knit patterns for Non-developable surfaces -- Voxel Fields as data representations A Method for Flexible Data Sampling of CFD data sets -- Survey-based Simulation of User Satisfaction for Generative Design in Architecture -- Design Tools and Workflows for Braided Structures -- Monolithic Earthen Shells Digital Fabrication: Hybrid Workflow -- A tool for optimizing conceptual mass design and orientation for rain water harvesting facades -- Assessment of RANS turbulence models in urban environments: CFD simulation of airflow around idealized high-rise morphologies -- Index.
Keywords: Buildings -- Design and construction; Mechanics, Applied; Solids; Computer-aided engineering; Energy policy; Energy and state; Building Construction and Design; Solid Mechanics; Computer-Aided Engineering (CAD, CAE) and Design; Energy Policy, Economics and Management